Pengaruh Omnichannel Marketing, Product Assortment, dan Online Customer Review terhadap Minat Beli Konsumen Mixue di Kota Medan (Jurnal Manajemen Kreatif dan Inovasi, 2025)
The food and beverage (F&B) industry in Indonesia has experienced rapid growth, particularly in the ice cream and frozen dessert subsector, marked by increasing sales and intensifying competition. This development requires businesses, including Mixue, to implement effective marketing strategies through the integration of digital and physical channels (Omnichannel Marketing), product assortment, and online customer reviews. This study employs a quantitative causal-associative approach using survey questionnaires analyzed with multiple linear regression to examine the influence of these variables on Mixue consumers’ purchase intention in Medan. The results indicate that Omnichannel Marketing and online customer reviews have a positive and significant effect on purchase intention, while product assortment has a positive but non-significant effect. The dominant indicator in purchase intention is exploratory interest, where consumers actively seek information and try new products. These findings emphasize that channel integration, information transparency, and product quality are key factors in enhancing consumer engagement and loyalty. Recommendations include strengthening omnichannel strategies, actively managing digital reviews, and innovating seasonal products to maintain purchase intention and expand market share.